2018
DOI: 10.1021/acs.jmedchem.7b01831
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity Affected by the Conformational Flexibility in Glycine–Lysine Based α-Helical Antimicrobial Peptides

Abstract: Antimicrobial peptides often show broad-spectrum activity due to a mechanism based on bacterial membrane disruption, which also reduces development of permanent resistance, a desirable characteristic in view of the escalating multidrug resistance problem. Host cell toxicity however requires design of artificial variants of natural AMPs to increase selectivity and reduce side effects. Kiadins were designed using rules obtained from natural peptides active against E. coli and a validated computational algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 51 publications
2
46
0
1
Order By: Relevance
“…This process causes a series of physiological changes. The morphological abnormalities of bacteria after treatment with these peptides has been observed by a range of microscopic approaches . Broadly speaking, antimicrobial peptides are more effective against bacteria than small organic molecules because they quickly recognize the negatively charged surface of the bacterial membrane and attack the phospholipid layer.…”
Section: Resultsmentioning
confidence: 99%
“…This process causes a series of physiological changes. The morphological abnormalities of bacteria after treatment with these peptides has been observed by a range of microscopic approaches . Broadly speaking, antimicrobial peptides are more effective against bacteria than small organic molecules because they quickly recognize the negatively charged surface of the bacterial membrane and attack the phospholipid layer.…”
Section: Resultsmentioning
confidence: 99%
“…The evolutionary basis for such residue preferences is unknown; however, there are intriguing hypothetical possibilities. Given their propensity to allow conformational freedom that deforms α-helical structure in aqueous environments, it is conceivable that glycine and alanine may allow peptides to remain in relatively unstructured, inactive (e.g., nontoxic) conformations before interacting with the microbial target (38). A number of studies have demonstrated that αHDPs can be unstructured in aqueous environments, adopting their strong α-helical conformation only upon encountering hydrophobic lipid membrane environments characteristic of microorganisms (2,17,18,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug-resistant clinical strains were obtained from the University Hospital Centre Split, Croatia. Their origin and antibiotic resistance phenotypes were described previously [37]. Antifungal activity was estimated against an environmental isolate of opportunistic pathogenic yeast Candida albicans and food isolates of food spoilage moulds Penicillium citrinum and Aspergillus niger.…”
Section: Bacterial Strainsmentioning
confidence: 99%